Impianti e sostituti meniscali - Olivieri, M.; Chicon Paez, D.; Turelli, L. (Lo Scalpello - Journal, 2019)
MENISCAL IMPLANTS AND SUBSTITUTESWhen meniscal lesions occur, preservation of meniscal tissue and restoration of the normal meniscal biomechanics isimperative to avoid early knee osteoarthritis; however, current surgical treatments for meniscal tears suffer fromsubsequent cartilage degeneration and inconsistent post-treatment results. When meniscal replacement is indicated,the desired implant should be chondroprotective; nevertheless, long-term effects of meniscal transplantation inprotecting the articular cartilage have not been fully elucidated as yet. To date, three clinical scaffolds that allow3-dimensional reconstruction of the meniscal structure (Menaflex CMI, Actifit® scaffold and NUsurface® MeniscusImplant) are available on the market for use, but additional data are needed to properly evaluate their safety andeffectiveness.